A Study on Insight of the Current Practices With Regards to Marketing Strategies In the Selected Banks: The Impact of Globalization and Technology on Marketing Strategies in Selected Banks (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The market developments kindled by liberalization andglobalization have resulted in changes in the intermediation role of banks. Thepace of transformation has been more significant in recent times withtechnology acting as a catalyst. While the banking system has done fairly wellin adjusting to the new market dynamics, greater challenges lie ahead.Financial sector would be opened up for greater international competition underWTO.